Delayed immune-related adverse events in assessment for dose-limiting toxicity in early phase immunotherapy trials. (January 2019) - Kanjanapan, Y.; Day, D.; Butler, M.O.; Wang, L.; Joshua, A.M.; Hogg, D.; Leighl, N.B.; Razak, A.R. Abdul; Hansen, A.R.; Boujos, S.; Chappell, M.; Chow, K.; et al.
Abstract: Background: Immunotherapy (IO) agents can cause late-onset immune-related adverse events (irAEs). In phase I trials, observation for dose-limiting toxicities (DLTs) is typically limited to the first cycle. The incidence of delayed-onset DLTs and their potential impact on dose determination have not been fully elucidated. Patients and methods: Consecutive patients enrolled in early phase IO trials at Princess Margaret Cancer Centre between August 2012 and September 2016 were retrospectively reviewed, applying trial-specific definitions for DLTs. A clinically significant AE (csAE) was defined as a treatment-related adverse event requiring corticosteroids, hormone replacement, IO delay or discontinuation. Results: A total of 352 consecutive trial enrolments in 21 early phase clinical trials were included. Two-hundred seventy-eight patients (79%) received monotherapy and 74 (21%) received combination IO. Two hundred sixty (74%) patients experienced irAEs. There were two protocol-defined DLTs. Twenty (5.7%) patients had 24 csAEs qualifying as DLTs except for occurrence after the protocol-specified DLT period. One-hundred and six (10%) of irAEs were csAEs, including endocrine (26%), respiratory (14%), gastrointestinal (11%), general (10%), dermatological (8%), hepatic (8%), musculoskeletal (6%), pancreatic (6%), haematological, metabolic, neurological, cardiac (each 2%), infective and ocular (each 1%) events. The highest risk of first-onset csAE was during the first 4 weeks compared with the period from 4 weeks to end of treatment (odds ratio 3.13, 95% confidence interval 1.95–5.02). The median time to first onset csAE was significantly shorter with combination than monotherapy IO (32 vs. 146 days, P < 0.001). Conclusions: In our series of early phase IO trials, the risk of csAE was highest during the initial 4 weeks on IO treatment, supporting the use of the conventional DLT period for dose escalation decision. However, there were 24 clinically significant late-onset DLTs in 5.7% of patients. Combination IO was associated with greater risk of and also earlier onset for csAE, which may need to be considered for early phase trial design. Highlights: Most clinically significant adverse events (csAEs) occur within the first 4 weeks of immunotherapy. Conventional dose-limiting toxicity (DLT) periods have relevance in early-phase immunotherapy trials. Late-onset DLTs occur with immunotherapeutic agents. Combination immunotherapies are associated with greater risk of and earlier onset of csAEs, compared with monotherapy.